A portable lateral flow distance-based paper sensor for drinking water hardness test - Liu, Yulin; Dong, Longzhan; Wu, Wenli; Ping, Jiantao; Chen, Jingbo; Hu, Qiongzheng (PloS one, 2024)
Hardness is one of the basic parameters of water, and a high-level hardness of drinking water may be harmful to human health. Thus, it is very important to monitor drinking water hardness. In this work, a portable lateral flow distance-based paper sensor for the semi-quantitative detection of drinking water hardness is demonstrated. In the presence of Ca 2+ /Mg 2+ , the hydrogel can be formed via the chelation between sodium alginate and Ca 2+ /Mg 2+ , inducing a phase separation process. The viscosity change of the sodium alginate solution is directly related to the Ca 2+ /Mg 2+ concentration and can be determined by the water lateral flow distance on test strips. The sensor successfully realizes the quantification of Ca 2+ and Mg 2+ in the range of 0–10 mmol L -1 and 4–20 mmol L -1 , respectively. The recoveries are found varied from 95% to 108.9%. The water hardness is acceptable for drinking if the C r values lies in the range of 0.259 to 0.419, and it is high with the C r value above 0.595. Remarkably, the performance of the sensor is comparable with the commercial kit for real water samples, which avoids the subjective judgment. Overall, this method provides a portable approach for semi-quantitative detection of drinking water hardness with the merits of convenience and low cost, which shows great potential for the potential application.